Mechanoreceptors in the Anterior Horn of the Equine Medial Meniscus: an Immunohistochemical Approach. (23rd April 2015) - Nemery, E.; Gabriel, A.; Grulke, S.; Piret, J.; Toppets, V.; Antoine, N.
Summary: Lameness due to stifle and especially meniscal lesions is frequent in equine species. In humans, mechanoreceptors involved in proprioceptive function are well studied. Given the high incidence of meniscal injuries in horses, and the lack of information concerning them in equine menisci, our objective was to study these corpuscles in six healthy anterior horns of the equine medial meniscus, which is the most common localisation reported for equine meniscal injuries. Immunohistochemical stainings were performed using antibodies against high molecular weight neurofilaments and glial fibrillary acidic proteins. From a purely fundamental point of view, our work highlights for the first time the presence of Ruffini, Pacini and Golgi corpuscles in equine meniscus. They were found, isolated or in clusters and always located at the vicinity of blood vessels, at the level of the anterior horn of the equine medial meniscus. This morphological approach could serve as a basis for clinical studies, to evaluate the impact of these corpuscles on the poor sportive prognosis in equine meniscal tears.